Effectiveness of implementation of sickle cell disease referral guidelines and other measures in paediatric department at a tertiary hospital in Saudi Arabia - Muhammad Matloob Alam; Abdulrhman Alathaibi; Hamdan Alghamdi; Jean Barrientos De Asis; Reynan Bautista; Mansour Aladwani; Mustafa Mohamed Selim (BMJ Open Quality)
Background Sickle cell disease (SCD) is an autosomal recessive genetic blood disorder. It affects up to 2.6% of the Kingdom of Saudi Arabia population.Local problem The paediatric haematology/oncology (PHO) team noticed that 75% of paediatric patients were inappropriately referred to the PHO department. Also, 86% of patients were investigated with unnecessary investigations followed by outpatient haematological clinic visits which cause financial burden to the hospital, job load for medical staff and psychological burden for families.Methods and interventions We carried out an initial audit of PHO referrals and requested laboratory tests over a 3-month period (October–December 2022). The PHO team developed a Clinical Pathway Guidelines (CPG), algorithm for early SCD detection and consultation form for suspected patients with SCD. Staff education about the new CPG was done. In addition, a dedicated PHO physician was assigned to map all referrals and provide rapid responses or outpatient department appointment dates for daily consultations and referrals. Furthermore, posters illustrating the algorithm for early SCD detection were printed and distributed to various units.Results The percentage of inappropriately referred patients improved during the three-quarters to reach above the desired target of 10%. This per cent reached 0% by the end of Q3 September 2023, indicating a sustainable improvement. Also, the per cent of unnecessary laboratory tests decreased from 86% before starting the project to 0% by the end of Q3. Finally, the number of wrong outpatient haematology visits decreased from 2 to 4 visits/week to 0 visits.Conclusions Staff education and adherence to guidelines are major priorities for the implementation of SCD referral guidelines in the paediatric department. This improves the utilisation of hospital resources, decreases the staff workload, hospital costs for unnecessary investigations and enhances the psychological care for families of patients with SCD.